A Foreign Policy Actor of Importance? The Role of the Somali Diaspora in Shaping Norwegian Policy towards Somalia. Issue 1 (4th December 2017) - Tellander, Ebba; Horst, Cindy
Abstract: In this article we explore the role of the Somali diaspora in Norwegian foreign policy towards Somalia through an in-depth case study. This empirical study sheds new light on the foreign policy impact of ethnic lobby groups by demonstrating three important points: 1) diaspora organizational strength can only be understood fully by taking a transnational approach, 2) diaspora lobbying attempts depend on interaction between diaspora and decision makers, and 3) in order to understand the potential success of diaspora lobbying, internal fragmentation as well as potential points of agreement need to be recognized. In order to incorporate these points, we suggest a theoretical model that bridges literature on the foreign policy impact of ethnic lobby groups and work on the transnational political ties of migrants. Our model adds the transnational ties and resources of diaspora and feedback loops between states and diaspora into ethnic lobby literature models on conditions for successful lobbying. This model will benefit future studies on the role of other diaspora groups in foreign policy formation towards their country of origin.